2011
DOI: 10.1183/09031936.00172910
|View full text |Cite
|
Sign up to set email alerts
|

Physician judgement is a crucial adjunct to pneumonia severity scores in low-risk patients

Abstract: This study investigates the reasons for hospitalisation in patients with low-risk (CURB-65 score 0-1) community-acquired pneumonia (CAP), with a view to identifying the potential for improving outpatient management.As part of a prospective observational study of CAP, we evaluated reasons for hospitalisation in these low-risk patients.565 patients had low-risk CAP and 420 of these were admitted (for .12 h). 39.3% had additional markers of severity justifying admission, 29.5% of the admissions were required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
(30 reference statements)
3
24
0
2
Order By: Relevance
“…We agree with CHOUDHURY et al [1] that more patients (18-20%) could be managed at home by family practitioners with the application of current guidelines, but we would like to comment that a greater number of patients (approximately 60%) could be managed at home with additional supported home-based care.…”
Section: To the Editorssupporting
confidence: 50%
“…We agree with CHOUDHURY et al [1] that more patients (18-20%) could be managed at home by family practitioners with the application of current guidelines, but we would like to comment that a greater number of patients (approximately 60%) could be managed at home with additional supported home-based care.…”
Section: To the Editorssupporting
confidence: 50%
“…Previous studies have shown that clinical judgment plays an important role in decisionmaking because severity of illness scores do not capture all important clinical risk factors to determine that most appropriate site for treatment (11). However, previous studies (12,13,16,21) are limited by several factors: (I) retrospective design; (II) small sample size; (III) different severity of illness scores; (IV) influence of physician preferences; (V) local hospital practices; and (VI) active participation in an intervention trial (23)(24)(25).…”
Section: Introductionmentioning
confidence: 80%
“…Several studies have evaluated the reasons why clinicians do not rely solely on pneumonia severity of illness scores to determine inpatient vs. outpatient treatment for CAP patients (16,18,21,22). Previous studies have shown that clinical judgment plays an important role in decisionmaking because severity of illness scores do not capture all important clinical risk factors to determine that most appropriate site for treatment (11).…”
Section: Introductionmentioning
confidence: 99%
“…17 This can simplistically be seen as lack of compliance with guidelines, but is likely to also reflect the significant limitations of CURB65 as a useful clinical tool. 46 Almost 40% of the "low-risk" patients that are hospitalized have other severity markers that may drive physicians to use broader-spectrum treatment, and some even require ICU admission. 46 In addition, despite the recommendation to withhold atypical coverage for macrolides in this group, atypical pathogens are actually most common in patients with CURB65 score 0 to 1.…”
Section: Severity-guided Treatmentmentioning
confidence: 99%
“…46 Almost 40% of the "low-risk" patients that are hospitalized have other severity markers that may drive physicians to use broader-spectrum treatment, and some even require ICU admission. 46 In addition, despite the recommendation to withhold atypical coverage for macrolides in this group, atypical pathogens are actually most common in patients with CURB65 score 0 to 1. 50 A recent randomized trial has also failed to show noninferiority of beta-lactam monotherapy in CAP patients because of a higher risk of treatment failure in patients with atypical pathogens not treated with macrolides.…”
Section: Severity-guided Treatmentmentioning
confidence: 99%